1998
DOI: 10.1530/eje.0.1380041
|View full text |Cite
|
Sign up to set email alerts
|

Role of conventional ultrasonography and color flow-doppler sonography in predicting malignancy in 'cold' thyroid nodules

Abstract: The aim of the present study was to establish the usefulness of conventional thyroid ultrasonography (US) and color flow-doppler (CFD) sonography in the assessment of 'cold' thyroid nodules. One hundred and four consecutive patients with thyroid nodules who were to undergo surgery were examined by US and CFD before thyroidectomy. Conventional US evaluated the presence of a halo sign, hypoechogenicity and microcalcifications. The vascular pattern on CFD was classified as follows: Type I, absence of blood flow; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
218
6
15

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(266 citation statements)
references
References 23 publications
27
218
6
15
Order By: Relevance
“…Of these, 235 studies were retrieved for further investigation, and 41 studies (14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54) met the final selection criteria and were included in the analysis. All 41 studies were observational studies published in peer-reviewed journals between 1989 and 2012.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Of these, 235 studies were retrieved for further investigation, and 41 studies (14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54) met the final selection criteria and were included in the analysis. All 41 studies were observational studies published in peer-reviewed journals between 1989 and 2012.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…In contrast, other studies have reported that certain characteristics on Doppler US including vascular pattern, resistive index (RI) and maximal systolic velocity (MSV) are not useful parameters for distinguishing malignant from benign solid nodules (24)(25)(26). These characteristics, therefore, should not be used as diagnostic tools to determine which nodules should undergo FNAB (27).…”
Section: Thyroid Ultrasonographymentioning
confidence: 99%
“…[23,29,30] An innumerable studies suggested that unnecessary invasive procedures can be avoided by using ultrasonography for the diagnosis of nodes of thyroids. [31][32][33][34] Findings of the present study showed that the positive predictive value was 50% while the negative predictive value was 47%. These findings are very similar to the previous study of Leenhardt L et al as they observed that a nodule with hypoechogenicity has a moderate positive predictive value (up to 63%) for malignancy with 75% sensitivity and 83% specificity.…”
Section: Discussionmentioning
confidence: 47%